2021
DOI: 10.1155/2021/5517567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Stimulation in the Field of Oral Health

Abstract: Physical stimulation has been widely used in clinical medicine and healthcare due to its noninvasiveness. The main applications of physical stimulation in the oral cavity include laser, ultrasound, magnetic field, and vibration, which have photothermal, cavitation, magnetocaloric, and mechanical effects, respectively. In addition, the above four stimulations with their unique biological effects, which can play a role at the gene, protein, and cell levels, can provide new methods for the treatment and preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…Other review articles from Qi et al [26] and Lew et al [17] focused on the application of magnetic fields in implant dentistry, highlighting, similar to that which emerged from the present review, some positive effects exerted by SFM and PEMF on dental implant osseointegration. Qi et al, however, dealt exclusively with PEMF stimulation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Other review articles from Qi et al [26] and Lew et al [17] focused on the application of magnetic fields in implant dentistry, highlighting, similar to that which emerged from the present review, some positive effects exerted by SFM and PEMF on dental implant osseointegration. Qi et al, however, dealt exclusively with PEMF stimulation.…”
Section: Discussionsupporting
confidence: 72%
“…Following this key step, the application of Electromagnetic and Magnetic Fields (EMFs and MFs) was proposed to further improve tissue healing and regeneration [17,18]. In fact, MFs are known to promote osteogenesis and many preclinical and clinical studies have demonstrated the effects of magnetism on bone healing [19][20][21][22][23][24][25], and the results from orthopedic applications have strongly encouraged the study of their use in dentistry to promote the osseointegration of dental implants [17,26].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, substantial and growing evidence has emerged showing that PEMF therapy as an alternative non-invasive method is able to provide a satisfactory therapeutic effect in a wide range of bone diseases. The basic principle of the pulsed magnetic field is to influence cell differentiation and proliferation by influencing various metabolic pathways, stimulate angiogenesis and bone formation, and thus promote fracture healing [35]. Stimulation of PEMFs has been shown to promote the proliferation and mineralization of osteoblasts in vitro, as well as to inhibit osteoclastogenesis.…”
Section: Reparative Regeneration Of Bone Tissue and Modern Trends In ...mentioning
confidence: 99%
“…Physical intervention is a common approach to preventing and treating dental calculus. Ultrasound relies on cavitation and acoustic microstreaming to achieve cleaning 60 . Shockwaves generated by lasers alter biofilm permeability to enable easier elimination of pathogenic bacteria 61 .…”
Section: Novel Prevention and Treatment Strategies For Dental Calculusmentioning
confidence: 99%